A commentary review of the cost effectiveness of manual therapies for neck and low back pain. Issue 3 (July 2017) - Harper, Brent; Jagger, Kristen; Aron, Adrian; Steinbeck, Larry; Stecco, Antonio
Summary: Background & purpose: Neck and low back pain (NLBP) are global health problems, which diminish quality of life and consume vast economic resources. Cost effectiveness in healthcare is the minimal amount spent to obtain acceptable outcomes. Studies on manual therapies often fail to identify which manual therapy intervention or combinations with other interventions is the most cost effective. The purpose of this commentary is to sample the dialogue within the literature on the cost effectiveness of evidence-based manual therapies with a particular focus on the neck and low back regions. Methods: This commentary identifies and presents the available literature on the cost effectiveness of manual therapies for NLBP. Key words searched were neck and low back pain, cost effectiveness, and manual therapy to select evidence-based articles. Eight articles were identified and presented for discussion. Results: The lack of homogeneity, in the available literature, makes difficult any valid comparison among the various cost effectiveness studies. Discussion: Potential outcome bias in each study is dependent upon the lens through which it is evaluated. If evaluated from a societal perspective, the conclusion slants toward "adequate" interventions in an effort to decrease costs rather than toward the most efficacious interventions with the best outcomes. When cost data are assessed according to a healthcare (or individual) perspective, greater value is placed on quality of life, the patient's beliefs, and the "willingness to pay."